In the Shadow of Hitler : Alabama's Jews, the Second World War, and the Holocaust - Puckett, Dan J. (Book collections on Project MUSE., 2013)
In the Shadow of Hitler is the first comprehensive state study of how southern Jews-and non-Jews-dealt with the coming of the Good War and the Nazi persecution of European Jews. In 1982, the Orthodox congregation of Ahavas Chesed in Mobile, Alabama, reconsecrated a Torah scroll from the Altneuschule in Prague, Czechoslovakia, that had been seized by the Nazis in the midst of the Holocaust. The Nazis, over the course of their occupation of Czechoslovakia, confiscated from Jewish communities throughout Bohemia and Moravia 1,564 Torahs, among numerous other Judaic ceremonial.